Glycemic Variability in Different Stages of Chronic Kidney Disease with Type 2 Diabetes Mellitus: A Cross-sectional Study - Sapna Gupta; Nivedita Priya (Indian Journal of Medical Biochemistry)
Aim and background: Hemoglobin A1c levels and complete blood count (CBC) is a diagnostic test used for diabetes and to determine the development of diabetic complications. The level of HbA1c is affected by factors, such as the Hb, the age of red blood cells (RBCs) in the blood circulation, and the Hb glycation rate. Our study aims to assess glycemic variability (GV) in diabetic patients at different stages of chronic kidney disease (CKD) and its relation to Hb and RBC levels to their HbA1c in different CKD stages. Materials and methods: This was a cross-sectional analysis of 156 adults with type 2 diabetes mellitus (T2DM) carried out in Parul Sevashram Hospital, Vadodara from November 2022 to May 2023. Chronic kidney disease stages were defined according to the modification of diet in renal disease (MDRD) equation stages I-V. HbA1c, RBC count, and RBS were estimated for the patients belonging to each stage. Statistical analyses were performed using SPSS software version 26.0 and Microsoft Excel 2019. Results: Out of the total diagnosed patients (n = 156), 58.3% were males and 41.6% were females. It was important to note that the maximum number of patients in the end-stage, that is, stage V, was detected with the HbA1c range of 4–7%. The inconsistencies in blood sugar levels with HbA1c were an alarming indication of other underlying issues such as renal anemia. Conclusion: Chronic kidney disease occurs due to diabetes and hypertension also contributes to renal anemia. In the later stages of CKD with T2DM, a low level of HbA1c ranging from 4 to 7% has been found due to low RBC count and Hb. Therefore, the clinical significance of this study is the non-reliability of HbA1c tests in advanced stages of CKD patients because of lower RBC counts giving rise to false glycated hemoglobin percentage.